Postpneumonectomy Empyema in the Presence of COVID-19 Pneumonia after Non-COVID-19 ARDS - Leneis, Veronika; Nemeth, Attila; Schlensak, Christian; Steger, Volker (The Thoracic and Cardiovascular Surgeon Reports, 2023)
Development of pleural empyema with or without bronchopleural fistula following pneumonectomy presents a major complication with a mortality of 10 to 20%. The surgical goals of bronchopleural fistula treatment are infection control, pus drainage, and lung re-expansion. The main goal is closure of the fistula. This can be achieved with various surgical methods, such as the Clagett or accelerated Weder procedure, omentoplasty, or a transpericardial approach, according to Abruzzini. We present the case of a 58-year-old patient with pleural empyema within the postpneumonectomy cavity in the presence of severe COVID-19 pneumonia after non-COVID-19 acute respiratory distress syndrome (ARDS) and extracorporeal membrane oxygenation (ECMO) therapy. The patient had undergone right-sided pneumonectomy for destroyed lung syndrome after invasive pulmonary aspergillosis
Keywords: pleural empyema; pyothorax; SARS COVID-19 infection; pneumonectomy; aspergillosis; bronchial stump insufficiency